The Musical Styles Of The Berawan People Within The Upper Reaches Of Sungai Bunut, Sarawak, East Malaysia - Sie Ai, Ng; Din, A. R.; Lawrence, R.; Satot, W. (Peat Swamp Forest Project, UNDP/GEF Funded (MALl99/G31), Sarawak Forest Department arid- -Institute of Biodiversity and Environmental Conservation, Universiti Malaysia Sarawak.., 2006)
This paper accompanies the production of a 20-minute observational documentary titled "Voices of Loagan Bunut". This document presents a series of cultural and personal portraits of Iban, Berawan and Penan musicians, singers and dancers living in the periphery of Loagan Bunut National Park (LBNP), Sarawak It also demonstrates the social finctions of traditional music in the context of this contemporary era of rapid modemisation. The documentary portrays two objectives. Firstly, the music traditions of the communities, which include the role of music in the culture and society, musical instruments and various forms of songs and dances. Secondly, it aims to highlight the current predicament faced by the musicians and their music. The digital recording media deployed ensures that historical data on the Iban, Berawan and Penan music and culture are more broadly disseminated and hence, appreciated.